Effective Factors on Durability of Family Physicians in Rafsanjan University of Medical Sciences - Ahmad Jamalizadeh; Zayne Haydaripour; Mostafa Nasirzadeh; Mehdi Rezaii; Ali Ahmadi; Fatameh Nezhadtorshab; Zahra Esmaili; Mina Hoseini (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2020)
Background: The durability of physicians working in the family physician program is one of the most important factors in effective implementation of this program. This study aimed to investigate the individual, organizational, and environmental factors affecting the family physicians' durability in Rafsanjan University of Medical Sciences in 2019. Methods: This descriptive-analytical study was conducted using census method among family physicians active in Rafsanjan rural family physician program during 2013-2017. The data collection tool included a questionnaire designed by experienced experts in the field of family physician program that contained the participants' demographic characteristics as well as organizational and environmental factors. The questionnaire's validity and reliability were confirmed by cronbach's alpha of 0.86. The questionnaires were completed through interviews and the collected data were analyzed by SPSS 16 using Chi-square and logistic regression tests. Results: Based on the findings, 53 (84 %) physicians were female and 10 (16 %) were males. The average age of participants was 32.62 years and their average collaboration lasted about 36.83 months. The family physicians' durability was inversely associated with their interests in 'continuing education', 'being single', 'camping outdoor' and 'doing something else' (p < 0.05). The results of logistic regression showed the physicians' interest in continuing education as the most important factor in their lack of durability. Conclusion: According to the results, consideration of personal factors, in comparison with other factors, has a great effect on the durability of family physicians.